Population-based study of factors predicting treatment intention in patients with locally recurrent rectal cancer. Issue 13 (12th October 2017) - Westberg, K; Palmer, G; Hjern, F; Nordenvall, C; Johansson, H; Holm, T; Martling, A
Abstract: Background: Local recurrence of rectal cancer (LRRC) is associated with poor survival unless curative treatment is performed. The aim of this study was to investigate predictive factors for treatment with curative intent in patients with LRRC. Methods: Population-based data for patients treated for primary rectal cancer between 1995 and 2002, and with LRRC reported as first event were collected from the Swedish Colorectal Cancer Registry and medical records. The associations between patient-, primary tumour- and LRRC-related factors and intention of the treatment for LRRC were determined. The impact of the identified predictive factors on prognosis after treatment with curative intent was also assessed. Results: A total of 426 patients were included in the study, of whom 149 (35·0 per cent) received treatment with curative intent. Factors significantly associated with treatment of the LRRC with palliative intent were primary surgery with abdominoperineal resection (odds ratio (OR) 5·16, 95 per cent c.i. 2·97 to 8·97), age at diagnosis of LRRC at least 80 years (OR 4·82, 2·37 to 9·80), symptoms at diagnosis (OR 2·79, 1·56 to 5·01) and non-central location of the LRRC (OR 1·79, 1·15 to 2·79). The overall 5-year survival rate was 8·9 per cent for all patients and 23·1 per cent among those treated with curative intent. In patients treated with curative intent, factors associated with increased risk of death were age 80 years or more (hazard ratio (HR) 2·44, 95 per cent c.i. 1·55 to 3·86), presence of symptoms (HR 1·92, 1·20 to 3·05), non-central tumour location (HR 1·51, 1·01 to 2·26) and presence of hydronephrosis (HR 2·02, 1·18 to 3·44). Conclusion: Non-central location of the LRRC, presence of symptoms and age at least 80 years at diagnosis of the LRRC were associated with treatment with palliative intent. Abstract : Defines good selection criteria